Importance of "meal first" strategy and effective situations of supplement use in elite athletes: Japan high performance sport center position stand - Yasuda, J.; Myoenzono, K.; Takai, E.; Toguchi, M.; Tsunezumi, S.; Kondo, C.; Kaizaki, A.; Ode, S.; Ohno, H.; Namma-Motonaga, K.; Kamei, A. (Frontiers in Sports and Active Living, 2023)
The "meal first" strategy is traditionally recommended for athletes' conditioning. However, the importance of the "meal first" principle has not been detailly well documented in athletes' lives. Supplement use has recently become a common part of athletes' diets, but unmonitored supplement use can cause negative consequences, such as anti-doping violations and health issues. Therefore, this review summarizes how the "meal first" strategy and planned supplement use are important for enhancing athletes` health and performance. We believe that the "meal first" strategy is beneficial in terms of the following aspects: (1) consumption of multi-nutrients and other functional components simultaneously; (2) positive effects on psychological well-being; (3) contribution to athletes' health by way of mastication; and (4) less risk for anti-doping violations. Before supplement use, we recommend that athletes first verify their basic factors (e.g., diet, training, and sleep), given that the benefits of supplements are examined and demonstrated with the control of those factors. Otherwise, athletes cannot obtain maximal benefits from the supplements. In contrast, there are situations in which supplements in athletes' lives can be advantageous, such as (1) nutrient deficiency due to ongoing dietary characteristics; (2) interruption of meals due to disease; (3) inaccessibility of quality food during athletic travel; (4) difficulty preparing food due to societal restrictions associated with disasters or infection outbreaks; (5) having a meal before, during, or after exercise is difficult; and (6) achieving targeted intake of performance-enhancing ingredients is not practical. In summary, we emphasize that the "meal first" strategy is recommended for athletes' conditioning, but there are several contexts when supplement use can be more useful in athletes' lives.